Facemasks, material and metaphors: An analysis of socio-material dynamics of the COVID-19 pandemic - Böhrer, Annerose; Döbler, Marie-Kristin; Tarkkala, Heta (Sociological Review, 2023)
In 2020, not only did the Sars-Cov-2 virus become a global pandemic, but public life also changed in the wake of various infection control measures. Increased use of masks was one of the first clearly visible changes. With the masks came stories about masks. Who wore them, where people should wear them, and why? It quickly became clear, however, that stories about ‘the facemask’ also have a metaphorical content, negotiating not only problems of the pandemic as a social crisis, but also other social issues amalgamated through the use of masks and the surrounding narratives. Thus, masks not only prevented infection, but also fed and materialised the public imaginary of the pandemic and its challenges. From this perspective, we explore three exemplary cases from Germany and Finland in 2020 in which the mask played different roles as a socio-material phenomenon, linking theoretical perspectives on materiality and metaphors. Additionally, the analysis presents illustrations done by a visual artist. These illustrations capture the key content of the analysis in the form of drawings.
CRIS-Team Scopus Importer:2023-04-07
Keywords: COVID-19; facemasks; materiality; metaphors; pandemic storytelling